Establishment and validation of a nomogram for predicting postoperative intestinal adhesion in children with acute appendicitis - Dezhao Liu; Yuchi Wang; Liyun Sun; Lijia Pan; Junkui Wang; Ying Lu; Zhao Cui; Jingying Li; Hui Geng (BMC, 2024)
Abstract Purpose This study aims to explore the value of multiple indicators in the evaluation of risk factors for intestinal adhesion (IA) after appendectomy in children with acute appendicitis (AA). Methods A retrospective study was conducted on 608 patients who underwent appendectomy in the Department of Pediatric Surgery, Children's Medical Center of Jilin Province from January 2017 to April 2023, with a one-year follow-up period to record the occurrence of IA after appendectomy. Univariate and multivariate analysis were used to screen the risk factors of postoperative IA, and a prediction model was established to predict postoperative IA. Results There were 527 patients in the non-IA group and 81 patients in the IA group. Binary Logistic regression was used to determine the strength of correlation with postoperative intestinal adhesion. The risk factors identified were as follows: DS ≥ 43 h (OR = 3.903, 5points), CRP ≥ 65 mg/L (OR = 3.424, 4.5points), PCT ≥ 0.9 µg/L (OR = 8.683, 8points), Surgical duration ≥ 100 min (OR = 6.457, 7points), Appendiceal perforation (OR = 6.073, 6.5points), Postoperative exhaust time ≥ 55 h (OR = 14.483, 10points). After test, the nomogram drawn based on binary logistic regression can obtain good prediction efficiency. In the training set, the area under the curve was 0.960, the sensitivity was 0.898, and the specificity was 0.905. In the test set, the area under the curve was 0.957, the sensitivity was 0.864, and the specificity was 0.906. Conclusion Postoperative exhaust time ≥ 55 h has a high risk of IA after appendicitis surgery in children. Early recovery of intestinal peristalsis function is essential. This scoring model is a novel and promising method for predicting postoperative IA.